A Phenomenon of Anxiety as an Effect of Reading Literacy in English of Indonesia Learners’ Context - Zananda, Tiray Febria (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2021)
Anxiety, an unpleasant state of inner turmoil and apprehension, often accompanied by nervous behavior, has proved that effects on the reading English literacy of Indonesia foreign learners’ context. The anxious feeling gives negative attitudes toward reading since each single thing is easy to comprehend by involving emotional. In order to reduce the anxious feeling, reading atmosphere is important to be implemented in order to help the learners’ literacy in English increase. It is not only that providing materials that cope the familiar local culture in English language materials help students become aware of how their local cultures enriches their linguistic resources and social practices, thereby making their language learning meaningful.